Universal forms in digital media: Zelensky and the propagandistic use of Telegram. - Pineda, Antonio (2024)
In an international scenario of political crisis, and with democracies weakened by the impact of populism and disinformation, the Russian invasion of Ukraine in 2022 provides a new scenario for the reactivation of war propaganda strategies. This article analyzes the digital discourse of President of Ukraine Volodymyr Zelensky on Telegram—a messaging network that favors one-way communication, immediacy, and access to communities of followers—in terms of war propaganda during the first year of the conflict, focusing on variables such as propaganda functions and techniques, the representation of the leader and the enemy, or the use of national symbols. The data-gathering technique is content analysis, which is applied to the study of the 2,075 publications made by the Ukrainian leader in the period analyzed (February 24, 2022-February 23, 2023). Results indicate a strategic orientation towards the internationalization of the conflict and the defense of a management orientation based on the mobilization of Ukraine, as well as personalized leadership and the persistence of techniques and trends of classic war propaganda in the digital political discourse of the 21st century.